Targeting Protein Kinase G to Treat Cardiac Proteotoxicity - Oeing, Christian U.; Mishra, Sumita; Dunkerly-Eyring, Brittany L.; Ranek, Mark J. (Frontiers in Physiology, 2020)
Impaired or insufficient protein kinase G (PKG) signaling and protein quality control (PQC) are hallmarks of most forms of cardiac disease, including heart failure. Their dysregulation has been shown to contribute to and exacerbate cardiac hypertrophy and remodeling, reduced cell survival, and disease pathogenesis. Enhancement of PKG signaling and PQC are associated with improved cardiac function and survival in many pre-clinical models of heart disease. While many clinically used pharmacological approaches exist to stimulate PKG, there are no FDA-approved therapies to safely enhance cardiomyocyte PQC. The latter is predominantly due to our lack of knowledge and identification of proteins regulating cardiomyocyte PQC. Recently multiple studies have demonstrated that PKG regulates PQC in the heart, both during physiological and pathological states. These studies tested already FDA-approved pharmacological therapies to activate PKG, which enhanced cardiomyocyte PQC and alleviated cardiac disease. This review examines roles of PKG and PQC during disease pathogenesis, and summarizes the experimental and clinical data supporting the utility of stimulating PKG to target cardiac proteotoxicity.